The State of European National Identity After 1945 to The Present - Fatima Jasim Mohammed Ali; Raghaa Abdul Imam Fayez (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: Since the end of World War II, the question of national identity in Europe has become increasingly significant as the continent has undergone political, cultural, and demographic transformations. Specific Background: Massive waves of migration, particularly from the East and the Global South, have redefined the sociocultural landscape of European nations and raised complex questions regarding national belonging, citizenship, and racial integration. Knowledge Gap: Despite extensive studies on nationalism, few have examined how postwar migration and globalization have simultaneously shaped and destabilized European identity, producing tensions between cosmopolitanism and cultural preservation. Aims: This study aims to analyze the evolution of European national identity after 1945, focusing on the psychological and sociopolitical “neurosis” of nationalism in contemporary Europe, with special attention to France. Results: Findings reveal that while European societies promote values of democracy and equality, these ideals coexist with anxiety over cultural loss and demographic change, resulting in identity polarization. Novelty: The research highlights identity as a dynamic construct shaped by both colonial legacies and modern globalization forces, not a fixed cultural essence. Implications: Understanding Europe’s identity crisis offers insight into broader global patterns of nationalism, migration, and multicultural coexistence in the 21st century. Highlights: Postwar migration reshaped Europe’s national identity and social cohesion. Democratic ideals coexist with fears of cultural and demographic change. European identity remains dynamic, balancing unity and multicultural diversity. Keywords: European Identity, Nationalism, Migration, Globalization, Cultural Crisis